2015
DOI: 10.1002/acr.22502
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Systemic Lupus Erythematosus and Cutaneous Lupus Erythematosus in a Predominantly White Population in the United States

Abstract: Objective Epidemiologic studies comparing the incidence and prevalence of systemic lupus erythematosus (SLE) and isolated cutaneous lupus erythematosus (CLE) are few. Olmsted County, Minnesota provides a unique setting for such a study owing to resources of the Rochester Epidemiology Project. We sought to describe and compare the incidence and prevalence of SLE and CLE from 1993 to 2005. Methods SLE cases were identified from review of medical records and fulfilled the 1982 ACR classification criteria. CLE c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
2
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(116 citation statements)
references
References 47 publications
(41 reference statements)
8
91
2
9
Order By: Relevance
“…The prevalences of scleroderma in Detroit, Mich., USA [36], areas of Canada [37, 38], and South Australia [39] were higher than the prevalence reported in Olmsted County [10]. The prevalence of SLE varied considerably over the years in Olmsted County, but was similar to other white populations in Europe and the USA [1013, 4042]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalences of scleroderma in Detroit, Mich., USA [36], areas of Canada [37, 38], and South Australia [39] were higher than the prevalence reported in Olmsted County [10]. The prevalence of SLE varied considerably over the years in Olmsted County, but was similar to other white populations in Europe and the USA [1013, 4042]. …”
Section: Resultsmentioning
confidence: 99%
“…In Nobrega et al [14], combined SLE is defined as classic SLE (positive LE cell test and ≥3 major systemic manifestations of LE) plus rheumatoid arthritis with LE (previous rheumatoid arthritis with positive LE cell test and ≥3 major systemic manifestations of LE). As for Durosaro et al [15] and Jarukitsopa et al [13], both studies reported the point prevalence of cutaneous lupus erythematosus for the Olmsted County population in January 2006. Differences in these prevalences are due to differences in the methodology used in defining the denominator and in adjusting the population.…”
Section: Figmentioning
confidence: 94%
“…Cutaneous lupus erythematosus (CLE), defined as isolated cutaneous lupus lesions occurring in the absence of significant evidence of SLE, has a 2-to 3-fold higher prevalence than SLE, with a peak incidence in the seventh decade of life [7]. There are limited data on whether CLE affects cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…It was also seen that the incidence in women was much more (almost nine times more in women than in men) than that in men [71].…”
Section: Incidence and Prevalence Of Slementioning
confidence: 92%